Analysis of Al-Ibrīz Tafsir as Genotext in Al-Maḥallī's Tafsir: An Intertextuality Study on Surah Al-Fātiḥah - Amrulloh, Tri Febriandi (Institut Agama Islam Negeri (IAIN) Keiri, 2023)
This paper examined the interpretation of al-Maḥallī li Ma'rifat Āyāti al-Qur'ān wa Nuzulihā by Ahmad Mudjab Mahalli (1958-2003M). This interpretation was written in 1989, using the pegon script and Javanese manners. In interpreting the Qur'an, Ahmad Mudjab Mahalli certainly cannot be separated from the previous exegetical literature as support in processing the results of his interpretation. Therefore, this paper examined al-Ibrīz's interpretation and al-Mahalli's interpretation using the intertextuality theory introduced by Julia Kristeva, which in this study focuses on Surah al-Fātiḥah. Intertextual studies are considered an accurate analytical tool for commentary works that are claimed to be influenced by previous exegetical kinds of literature. The results of this study proved that the elements of al-Ibrīz's interpretation are contained in the QS. al-Fātiḥah in al-Mahalli's interpretation, namely, muqaddimah surah, verse 2, verse 4, and verse 7. While the principle of intertextuality used in processing al-Ibrīz's interpretation as its genotext found several principles including haplology, transformation, and expansion.